Dinamika Hoax, Post-Truth dan Response Reader Criticism di Dalam Rekonstruksi Kehidupan Beragama - Sonny Eli Zaluchu (Religió: Jurnal Studi Agama-agama, 2020)
This research is conducted through literature review to expose and analyze hoax phenomenon, post-truth paradigm, and reader-response criticism. This paper aims to elucidate the social extent to which hoaxes are formed as a result of the presence of post-truth paradigm in the mind of information waves as well as the impact of the digital revolution. The phenomenon will be described through hermeneutical method using reader-response criticism approach in the context of religious life. The research found that spiritual life can be developed in the right way through media-literacy, besides the spread of hoaxes, disinformation, and truth-oriented personal beliefs rather than facts.